2015
DOI: 10.1016/j.pharep.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone prevents morphine antinociceptive tolerance via ameliorating neuroinflammation in rat cerebral cortex

Abstract: It is concluded that oral administration of pioglitazone attenuates morphine-induced tolerance. This effect of pioglitazone may be, at least in part, due to its anti-inflammatory property which suppressed the cortical pro-inflammatory cytokine and inhibited of nuclear factor-kappa B activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Besides, our recently finding indicated that morphine augments both pro-inflammatory cytokines (e.g., TNF-α, IL-1β and IL-6) and NF-κB activity in the cerebral cortex of the rat, which was consistent with the behavioural manifestation of morphine analgesic tolerance. However, concurrent administration of the pioglitazone (40 mg/kg) hampered these effects of the morphine [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, our recently finding indicated that morphine augments both pro-inflammatory cytokines (e.g., TNF-α, IL-1β and IL-6) and NF-κB activity in the cerebral cortex of the rat, which was consistent with the behavioural manifestation of morphine analgesic tolerance. However, concurrent administration of the pioglitazone (40 mg/kg) hampered these effects of the morphine [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of PPAR signalling in the development or modulation of other chronic pain conditions, such as osteoarthritis, cancer pain and migraine requires further study, as does the interaction of PPAR signalling with other well‐characterized endogenous pain control systems and currently prescribed analgesics. On this latter point, the PPARγ agonist pioglitazone has been shown to attenuate tolerance to morphine in a rat model of inflammatory pain (Ghavimi et al ., , Ghavimi et al ., ) and in the mouse tail immersion test (de Guglielmo et al ., ). Similar potential synergistic antinociceptive interactions with the cannabinoid (Russo et al ., ) and TRPV1 (Ambrosino et al ., ) signalling systems have been reported.…”
Section: Future Perspectivesmentioning
confidence: 97%
“…Ghavimi et al (2015) found that the activities of proinflammatory cytokines (tumor necrosis factor alpha (TNF-α), interleukin (IL)-1β, and IL-6) and nuclear factorkappa B increased in the cerebral cortex of morphine-tolerant rats. On the one hand, the increased proinflammatory cytokines can interact with the opioid receptors and promote morphine tolerance.…”
Section: Figmentioning
confidence: 99%